Factors associated with malnutrition inflammation score among hemodialysis patients: A cross-sectional investigation in tertiary care hospital, Palestine. - Zakaria Hamdan; Zaher Nazzal; Fatima Masoud Al-Amouri; Sanaa Ishtayah; Sarah Sammoudi; Lawra Bsharat; Manal Badrasawi (PLoS ONE, 2025)
Malnutrition is a prevalent complication in hemodialysis patients and is associated with increased mortality and morbidity. This study aimed to identify the risk factors associated with malnutrition among hemodialysis patients including patient's general characteristics, functional status, and dietary intake. This study involved hemodialysis patients in An-Najah National University Hospital at Nablus/Palestine. An interview-based questionnaire was used to collect data related to sociodemographic, lifestyle, hemodialysis, medical history, anthropometrics, biochemical indices, dietary data using 3-days diet recall, and functional status. Malnutrition-inflammation score tool (MIS) was used for malnutrition screening of the studied patients. The study involved 188 patients, with a mean age of 57.8±14 years. A total of 28.2% participants are reported malnourished. Malnutrition was significantly associated with being female (p = 0.001), unemployed (p = 0.009), nonsmoker or ex-smoker (p = 0.018). Patients with CVDs (p = 0.006), higher months on dialysis (p = 0.002), lower BMI (p = 0.018), and using catheter for dialysis access are more likely to develop malnutrition (p = 0.018). Furthermore, patients with poor functional status (poor handgrip strength (p<0.001), inability to walk (p<0.001), needing help in daily activity or in transfer (p<0.001)) were significantly associated with malnutrition. Additionally, malnutrition was significantly higher among patients who does not meet their recommended calorie intake (p = 0.008), whose sodium intake within recommendation (p = 0.049), patients with low levels of hemoglobin (p = 0.022), albumin (p<0.001), TIBC (p = 0.002), phosphate (p<0.001), and patients with higher levels of ferritin (p<0.001). Higher months on dialysis (Exp(B) = 1.02), unmet calorie intake (Exp(B) = 4.3), needing help in daily activities (Exp(B) = 0.238), and low albumin level (Exp(B) = 0.048) were the independent predictors of malnutrition. This study highlights the significant association between malnutrition and various demographic, clinical, functional, and dietary factors in hemodialysis patients, revealing the burden of malnutrition during HD. It also necessitates targeted intervention to address these risk factors and improve nutritional status and the overall health outcomes of HD patients.